Development and application of force resultant models describing jack-up foundation behaviour - Cassidy, M; Martin, C; Houlsby, G (2004)
As jack-ups have moved into deeper and harsher waters there has been an increased need to understand jack-up behaviour and develop analysis techniques. One of the areas of significant development has been the modelling of spudcan footing performance, where the load-displacement behaviour of the footings is required to be included in any overall numerical model. Because they can be incorporated into conventional structural analysis programs, force resultant models based on strain-hardening plasticity theory are appropriate replacements for the unrealistic assumptions of pinned or linear spring footings. The development of these models for the analysis of spudcans on both clay and sand is reviewed here. A formulation for a six-degrees-of-freedom model that describes the load-displacement behaviour in the vertical, moment, horizontal, and torsion directions is also detailed. Using this model any load or deformation path can be applied to the footing and the corresponding unknowns (deformations or loads) calculated. This formulation allows the model to be implemented into three-dimensional structural analysis programs, and examples of this are given. Some future challenges in this area are addressed, including the development of models that account for cyclic loading behaviour. © 2004 Elsevier Ltd. All rights reserved.